Optimizing formation of fatty acid ester nanoemulsion systems for non-steroidal anti-inflammatory drug delivery - Mat Hadzir, Nursyamsyila (2012)
Pseudo-ternary phase diagrams for oleyl laurate, oleyl stearate and oleyl oleate with surfactants (Pluronic F68 and Span 20) and piroxicam were constructed. In each pseudo-ternary phase diagram, a one-phase region was located along the apex line of water and mixed surfactants. A multi-phase region was also formed and found to dominate the three pseudo-ternary phase diagrams. The formation of large multiphase regions was believed to be due to less or no synergistic effects between the Pluronic F68 and Span 20 in facilitating the formation of nanoemulsions. Even so, a composition from the multi-phase region from each pseudo-ternary phase diagram was chosen for preparing the nanoemulsions systems containing piroxicam via low energy emulsification methods. The incorporation of a rheology modifier (xanthan gum) into the nanoemulsions systems containing piroxicam successfully facilitated the formation of nanoemulsions systems. The results from the preliminary study via ‘One-At-A-Time Approach’ showed that the optimum amount (w/w) of oil for oleyl laurate nanoemulsions was 30 g (w/w) and 20 g (w/w) for oleyl stearate nanoemulsions and oleyl oleate nanoemulsions. For each nanoemulsions system, the mixed surfactants (Pluronic F68:Span 20, 8:2) and rheology modifier needed for the emulsification to take place was found to be 10 g (w/w) and 0.5 g (w/w), respectively. However, the emulsification process at optimum amount of the three variables for each nanoemulsions system showed that the low energy emulsification method was unable to form emulsions in the nano-size range. Thus, further investigation of the emulsification process was carried out using a high shear emulsification method by employing Artificial Neural Network (ANN) and Response Surface Methodology (RSM). ANN and RSM were used to predict the optimum amount (w/w) of oil, mixed surfactants and rheology modifier in order to produce nanoemulsions systems having ‘nano’-sized particles with high physical stability. The results showed that RSM gave a better prediction than ANN whereby a comparison between the predicted and experimental values showed good correspondence between them, with R2 values ³ 0.9. The good correspondence of predicted and experimental values indicated that the empirical models derived from RSM can be used to describe the relationship between the variables and responses for the emulsification process of palm-based nanoemulsions systems. As a result, the optimization of the emulsification process via a high shear emulsification method was performed by RSM based on Central Composite Design (CCD). The optimal amounts (w/w) of oleyl laurate, oleyl stearate and oleyl oleate as the oil phase for the oleyl laurate nanoemulsions (OL-Opt), oleyl stearate nanoemulsions (OS-Opt) and oleyl oleate nanoemulsions (OO-Opt) were found tobe 33.92 g, 17.74 g and 17.95 g, respectively. As for the mixed surfactants (Pluronic F68:Span 20, 8:2) and rheology modifier, the optimal amounts (w/w) were found to be 4.03 g (OL-Opt), 9.97 g (OS-Opt), 7.59 g (OO-Opt) and 0.71 g (OL-Opt), 0.57 g (OS-Opt) and 1.02 g (OO-Opt), respectively. The emulsification process via high shear emulsification method at optimal amounts of the three variables has produced emulsions in ‘nano’-sized particles with surface charge values more negative than -30 mV at pH around 5, which suggest high physical stability of the emulsions. The characterization of oleyl laurate nanoemulsions (OL-Opt), oleyl stearate nanoemulsions (OS-Opt) and oleyl oleate nanoemulsions (OO-Opt) showed that the particle sizes were in the nano-range (in between 50 and 200 nm), with surface charge values and pH of -32.7 to -40.6 mV and 5.08 to 5.14, respectively. From observations, the three nanoemulsions systems were also found to be stable at various storage temperatures, which were 3 °C, 25 °C and 45 °C, with no phase separations. The physically stable nanoemulsions systems were also found to exhibit non-Newtonian flow behaviour by displaying a pseudoplastic behavior and shearthinning properties. The conductivity values of OL-Opt (310.0 mS cm-1), OS-Opt (281.0 mS cm-1) and OO-Opt (413.0 mS cm-1) also confirmed that oil-in-water nanoemulsions have been successfully produced. They were also found to be nonirritant to the skin. The oleyl laurate nanoemulsions (OL-Opt), oleyl stearate nanoemulsions (OS-Opt) and oleyl oleate nanoemulsions (OO-Opt) were found to be stable for three months at various storage temperatures, which were 3 °C, 25 °C and 45 °C; and passed the Freeze-thaw cycle with no phase failures. The particle size analyses showed that there were no significant differences during the three months storage period especially at temperatures of 3 °C and 25 °C, which indicated that Ostwald ripening could be prevented from occurring by incorporating polymeric surfactants and rheology modifiers into the nanoemulsions systems. At storage temperature of 45 °C, the particle sizes for the three nanoemulsions systems were found to increase, which was probably due to the loss of water from the system, thus allowing the particles to combine and finally forming larger particles. The in-vitro study of OL-Opt, OS-Opt and OO-Opt was carried out by investigating their penetration through the cellulose synthetic membrane and Wistar male rat skin. It was found that the highest penetration of piroxicam at the 8th h was given by OSOpt (31.12%) followed by OO-Opt (25.46%) and OL-Opt (21.55%). The addition of 1% menthol (which was labeled as WE) to each nanoemulsions system has increased the amount of piroxicam passing through the cellulose synthetic membrane as oleyl stearate nanoemulsions with menthol (OS-OptWE) showed the highest penetration of piroxicam (35.65%) followed by oleyl oleate nanoemulsions with menthol (OO-OptWE) (30.54%) and oleyl laurate nanoemulsions with menthol (OL-OptWE) (25.15%). Finally, the release of piroxicam from OL-OptWE, OSOptWE and OO-OptWE was carried out via the rat skin. OS-OptWE was found to give the highest penetration of piroxicam (41.44%), followed by OO-OptWE (29.01%) and OL-OptWE (21.10%).